Mortality and Cardiovascular Disease Among Older Live Kidney Donors. Issue 8 (9th July 2014) - Reese, P. P.; Bloom, R. D.; Feldman, H. I.; Rosenbaum, P.; Wang, W.; Saynisch, P.; Tarsi, N. M.; Mukherjee, N.; Garg, A. X.; Mussell, A.; Shults, J.; Even‐Shoshan, O.; et al.
<x xml:space="preserve">Abstract</x> Over the past two decades, live kidney donation by older individuals (≥55 years) has become more common. Given the strong associations of older age with cardiovascular disease (CVD), nephrectomy could make older donors vulnerable to death and cardiovascular events. We performed a cohort study among older live kidney donors who were matched to healthy older individuals in the Health and Retirement Study. The primary outcome was mortality ascertained through national death registries. Secondary outcomes ascertained among pairs with Medicare coverage included death or CVD ascertained through Medicare claims data. During the period from 1996 to 2006, there were 5717 older donors in the United States. We matched 3368 donors 1:1 to older healthy nondonors. Among donors and matched pairs, the mean age was 59 years; 41% were male and 7% were black race. In median follow‐up of 7.8 years, mortality was not different between donors and matched pairs (p = 0.21). Among donors with Medicare, the combined outcome of death/CVD (p = 0.70) was also not different between donors and nondonors. In summary, carefully selected older kidney donors do not face a higher risk of death or CVD. These findings should be provided to older individuals considering live kidney donation.